The boyfriend project - Rochon, Farrah (Forever, 2020)
"Samiah Brooks never thought she would be "that" girl. But a live tweet of a horrific date just revealed the painful truth: she's been catfished by a three-timing jerk of a boyfriend. Suddenly Samiah-along with his two other "girlfriends," London and Taylor-have gone viral online. Now the three new besties are making a pact to spend the next six months investing in themselves. No men, no dating, and no worrying about their relationship status . . . For once Samiah is putting herself first, and that includes finally developing the app she's always dreamed of creating. Which is the exact moment she meets the deliciously sexy, honey-eyed Daniel Collins at work. What are the chances? When it comes to love, there's no such thing as a coincidence. But is Daniel really boyfriend material or is he maybe just a little too good to be true?"--